Pelatihan dan Pendampingan Pengelolaan Keuangan BumDes Tetus Kuanheun Kabupaten Kupang: Pengabdian - Tkela, Melianus E.; Maria Immaculata Bahantwelu; Yohana Febiani Angi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to improve the capacity of the Tetus Kuanheun Village-Owned Enterprise (BUMDes) management in transparent and accountable financial management, in accordance with the principles of good governance. The main problems faced by partners include manual and inconsistent recording of financial transactions, the lack of a standard financial report format, and the management's poor understanding of basic accounting principles. To address these issues, the activity was carried out through a three-day training and mentoring method, from August 5–7. The methods used included interactive lectures, group discussions, hands-on practice in recording transactions using Microsoft Excel, and mentoring in preparing simple financial reports. The results of the activity showed a significant increase in the participants' ability to understand basic accounting concepts, maintain digital financial records, and prepare financial reports more systematically and in accordance with standard formats. In addition, this activity succeeded in raising the management's awareness of the importance of the principles of transparency and accountability in managing village business funds. With follow-up in the form of ongoing monitoring and mentoring, it is hoped that BUMDes Tetus Kuanheun will be able to become a model for professional, transparent, and sustainable village financial management.